An Investigation of Students’ Perception of Assessment for Learning in Integrated Science: A Case Study of Potsin T. I. Ahmadiyya Senior High School - Agbene, Samuel; Baidoo, Usman; Stephen Atepor (MASI Mandiri Edukasi, 2023)
This study sought to investigate students’ perceptions of assessment for learning and the teaching strategies teachers employ in teaching integrated science. The students were sampled using stratified sampling techniques The sample for this study consisted of 215 senior high school third-year students. Students’ perceptions about assessment for learning were checked using Assessments Experience Questionnaires. The questionnaires were analyzed using descriptive statistics. The study found that students have a positive perception of assessment for learning. However, it emerged from the study that students are not assessed adequately in integrated science as prescribed in the science syllabus. Per the responses from the students, the teacher-centered approach seemed to dominate the teaching of integrated science instead of the student-centered approach as prescribed in the science syllabus. It is recommended that there should be proper supervision to ensure that students are well-assessed during the teaching and learning of integrated science. Again, this study for teaching integrated science implies that a specific teaching method (student-centered) or approach should be prescribed in the integrated science curriculum for teachers to use to improve students’ academic success in integrated science.